Using L-STM to directly visualize enzymatic self-assembly/disassembly of nanofibers. Issue 33 (5th August 2016) - Zheng, Zhen; Wang, Jihao; Chen, Peiyao; Xie, Maolin; Zhang, Lei; Hou, Yubin; Zhang, Xin; Jiang, Jun; Wang, Junfeng; Lu, Qingyou; Liang, Gaolin
Abstract : Homebuilt L-STM was employed for direct visualization of enzymatic self-assembly/disassembly of nanofibers at the molecular level in aqueous solution. Abstract : Self-assembly/disassembly is ubiquitous in nature and plays an important role in many biological events. But noninvasive characterization of this process in real time at molecular resolution remains challenging. Herein, using homebuilt liquid-phase scanning tunneling microscopy (L-STM) with ultrahigh stability, we directly visualized enzymatic self-assembly/disassembly of oligopeptide nanofibers in real time for the first time. Static high-resolution L-STM images clearly showed the molecular packing details in the supramolecular nanofiber and the diameter of the nanofiber was consistent with that of cryo transmission electron microscopy (cryo-TEM) observations. Moreover, the self-repairing behavior of the supramolecular nanofibers was also directly observed at high resolution for the first time. This work unprecedentedly revealed new insights into Nature-mimic self-assembly and disassembly at the molecular level. It also illustrates the potential of our homebuilt L-STM in studying delicate biological processes in physiological solution with high resolution.